2020
DOI: 10.3390/jcm9051334
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Enables Prediction of Cardiac Amyloidosis by Routine Laboratory Parameters: A Proof-of-Concept Study

Abstract: (1) Background: Cardiac amyloidosis (CA) is a rare and complex condition with poor prognosis. While novel therapies improve outcomes, many affected individuals remain undiagnosed due to a lack of awareness among clinicians. This study was undertaken to develop an expert-independent machine learning (ML) prediction model for CA relying on routinely determined laboratory parameters. (2) Methods: In a first step, we developed baseline linear models based on logistic regression. In a second step, we used an ML alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Goto et al [27] have proposed two CNN-based prediction models for ECG (CA, n = 130) and echocardiography (CA, n = 70) data, achieving 0.85 ROC AUC and 0.91 ROC AUC scores, respectively. Our group [28] built a gradient-boosted tree prediction model for routinely available lab parameters (CA, n = 121) and achieved an ROC AUC score of 0.86 on the test set. Martini et al [29] trained a CNN-based prediction model for LGE CMR images (CA, n = 107) and achieved an ROC AUC score of 0.982 on the test set.…”
Section: Role and Contribution Of Ai For Ca Diagnosismentioning
confidence: 99%
“…Goto et al [27] have proposed two CNN-based prediction models for ECG (CA, n = 130) and echocardiography (CA, n = 70) data, achieving 0.85 ROC AUC and 0.91 ROC AUC scores, respectively. Our group [28] built a gradient-boosted tree prediction model for routinely available lab parameters (CA, n = 121) and achieved an ROC AUC score of 0.86 on the test set. Martini et al [29] trained a CNN-based prediction model for LGE CMR images (CA, n = 107) and achieved an ROC AUC score of 0.982 on the test set.…”
Section: Role and Contribution Of Ai For Ca Diagnosismentioning
confidence: 99%
“…Although machine learning-based algorithms applied to the diagnosis of amyloidosis are not new. Machine learning-based algorithms have previously been applied to identify heart failure-related cardiac amyloidosis patients from heart failure-unrelated cardiac amyloidosis patients by the utilization of basic laboratory methods [ 22 ].To the best of our knowledge, the current study is the first to apply machine-learning to proteomics-based data for subtype classification of amyloidosis. In this work, SVMs were employed as it is a robust learning algorithm for classification with high discriminative power and insensitive to outliers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a proof-of-concept study showed that an expert-independent machine learning prediction model for CA relying on routinely determined laboratory parameters was able to generate a CA-related HF profile that may help increase disease awareness among physicians and improve timely diagnosis 34 . With the continuous improvement in machine learning techniques and the integration of imaging and laboratory parameters, this approach holds promise for the future.…”
Section: Advances In the Diagnosis Of Cardiac Amyloidosismentioning
confidence: 99%